2015
DOI: 10.4028/www.scientific.net/amm.788.46
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Technological Parameters of High-Precision Plasma Cutting on the Position of the Anode Spot on the Cut Edge

Abstract: The paper is devoted to investigating the position of the anode spot on the cut edge during high-precision plasma processing and studying the trajectory of the melting products flowing from the cut edge. The material of samples is structural steel of St3 (<strong>GOST 14637-89)</strong> having the thickness of 3, 4, 5, 6 and 8 mm. The formation of the cut edge was carried out according to the HiFocus technological scheme of cutting by using the equipment manufactured by the Kjellberg firm (Germany)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…The limit value of pressure and gas rate is determined by the chosen size type of a set of the plasmotron changeable parts. So, in determining technological parameters which influence the forming of the cut sides, it is possible to consider only the cutting speed as a controlling parameter [14,15]. At the preliminary stage before the description of the process, a number of experiments were conducted for determining the optimal value of the cutting speed at which the value of deviation from the cut perpendicularity is close to zero.…”
Section: Experimental Datamentioning
confidence: 99%
“…The limit value of pressure and gas rate is determined by the chosen size type of a set of the plasmotron changeable parts. So, in determining technological parameters which influence the forming of the cut sides, it is possible to consider only the cutting speed as a controlling parameter [14,15]. At the preliminary stage before the description of the process, a number of experiments were conducted for determining the optimal value of the cutting speed at which the value of deviation from the cut perpendicularity is close to zero.…”
Section: Experimental Datamentioning
confidence: 99%
“…As shown in paper [6], quality of the separating plasma cutting is characterized by the cut width, the magnitude of the non-perpendicular character of the lateral surfaces of the cut cavity, the roughness of the latter, the existence and size of a lattice, etc. From the point of view of thermophysics, the separating cutting of metals is the process of local heating, melting, and blowing of a metal from the frontal edge of the cut under exposure to the high temperature plasma jet [6]. In this case, the heat flow into a metal is predetermined by the radiant and convective heat exchange from the arc column, the arc spot, and a plasma jet behind the arc spot.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The disadvantages of these studies are the lack of examining the impact of process parameters on structural transformations in the cutting zone. Research reported in [5][6][7][8][9] was also aimed at determining the influence of technological characteristics of the process on such quality indicators as the width of cutting and a thermal impact zone.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations